Класифікація систем мобільного зв'язку загального користування - Шаламов, І. Є. (ХНУРЕ, 2020)
The mobile communication system is a set of technical means (radio equipment, switching devices, interconnectors and transmission systems) that allow mobile subscribers to communicate with each other as well as with subscribers. Mobile communication systems allow the transmission of information between radio stations of moving objects, both directly and by relaying through the base station.
Keywords: зв'язок; мобільний